Pengaruh Economic Value Added (Eva), Return On Asset (Roa), Return On Equity (Roe), Dan Net Profit Margin (Npm) Terhadap Harga Saham Perusahaan Food And Beverage Yang Terdaftar Di Bei Tahun 2016-2019 - Cicik Marianti; Ronny Malavia Mardani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT“This study aims to reveal the impact of Economic Value Added (EVA) Return On Asset (ROA), Return On Equity (ROE) and Net Profit Margin (NPM) popupation in this study are food and beverage companies listed on the IDX at 2016-2019 period. While the sampling technique uses puposive sampling. From population, 11 companies were sampled. Based on the results of data analysis, it can be concluded that EVA and ROA have a positive and significant effect on stock price. Meanwhile, ROE and NPM have no effect on stock prices. This research uses the method Purposive Sampling for sampling. Population in research this is all food and beverages on the Indonesian Stock Exchange during 2016-2019. From Overall 15 companies as a population obtained 11 companies as samples. Based on the findings of the date analysis, it was concluded that EVA, and ROA positive effect on stock prices. Mean while ROE, and NPM did not wash affect the stock price”. Keywords: Economic Value Added (EVA), Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and stok prices.